Factors related to coping with the COVID-19 pandemic by nursing students from higher education institutions - Santos, Janaina Luiza dos; Monteiro, Ana Claudia Moreira; Azevedo, Diana Paola Gutierrez Díaz; Breder, Alexandre Diniz; Pinheiro, Ana Beatriz Rodrigues; Rodrigues, Letícia Cristina Modesto; Fabio, Fabiana Lacerda; Azevedo, Kênia Suzana de; Pessanha, Pablo Pereira; Silva, Raphaela Moreira Gomes da (Seven Editora, 2023)
Objective: to analyze the coping/resilience strategies developed by students from two higher education institutions (HEIs) during the COVID-19 pandemic. Methods: a descriptive, cross-sectional study with a qualitative approach, carried out in two HEIs, one public and one private, located in the Norte Fluminense region of the state of Rio de Janeiro. The sample of students who answered the questionnaire was 140 from the public institution and 150 from the private institution. The IRAMUTEQ® software was used to generate the similarity analysis and word cloud. Results: Of the 290 participating students, it was identified that the majority belonged to the female sex, 84.5% (n=246) and 15.1% (n=44) were male, the age profile was from 17 to 58 years, where 7.2% (n=21) were in the age group of fewer than 20 years, 81.1% (n=236) in the age group of 20 to 39 years, and 11.3% (n=33) aged 40 to 59 years. Discussion: From the deep analysis we presented two categories 1 Adaptive capacity of undergraduate nursing students in the COVID-19 pandemic period and 2 Spirituality, interaction with friends and family decreases the deleterious effects of social isolation Conclusion: it was evidenced the adaptive capacity and spirituality, as well as friends and family, was fundamental, as a form of resilience; it is explicit that knowing how to deal with day-to-day difficulties, having a support network, remaining psychologically positive helps in solving problems in various areas of life. DOI:https://doi.org/ 10.56238/devopinterscie-224